Immune Dysfunction in Tourette Syndrome - Ishraga Elamin; Mark J. Edwards; Davide Martino (Behavioural Neurology)
The association between immunity and neurodevelopmental disorders has been extensively investigated in autism, suggesting a potential involvement of both cellular and humoral immunity in the establishment of synaptic connectivity modulation during development. A similar link has been proposed also for Tourette syndrome (TS), a complex, multifactorial disorder, in which the interplay between genetic, environmental, hormonal and immunological factors might be relevant. Lymphocyte subpopulation analysis in TS suggests a possible systemic activation of several T- and B-cell subtypes, whereas the observed decreased numbers of T regulatory lymphocytes might predispose to autoimmunity. Genes related to both cell- and antibody-mediated immune responses may be over-expressed at specific ages in youngsters with TS. Data from cytokine measurements and transcriptomics profiles in TS patients are coherent with the systemic immune activation detected by studies on lymphocyte subpopulations. Moreover, TS patients have exhibited IgG3 and IgA dysgammaglobulinemia, which might predispose to recurrent infections and autoimmunity. To date, the association between TS and autoantibodies has not been demonstrated. Interestingly, however, there is a higher degree of maternal family history of autoimmune diseases among TS patients. Finally, TS patients could be prone to allergic illnesses (asthma, atopic dermatitis, rhinitis, conjunctivitis), but more work is needed in this area.